Experimental investigation on flow instability of forced circulation in a mini-rectangular channel under rolling motion. (January 2016) - Yu, Zhiting; Tan, Sichao; Yuan, Hongsheng; Chen, Chong; Chen, Xianbing
Highlights: Flow instabilities under rolling condition were experimentally investigated. Intermittent flow boiling with rolling motion was found during rolling condition. Superposition of rolling motion and PDO was found and confirmed. The superposition depends on both additional forces and thermodynamic factors. Abstract: An experimental study was performed in a mini-rectangular channel under rolling condition to investigate the flow instability of forced circulation. In order to analyze the influence of rolling motion on two-phase flow instability, experiments under both static condition and rolling condition were conducted using the same thermodynamic parameters, such as flow rate, system pressure and inlet fluid temperature. During the experiments, typical pressure drop oscillation (PDO) was observed in static condition, while abundant experimental phenomena including single-phase flow fluctuation, trough-type flow oscillation, coupled flow oscillation and two-phase flow fluctuation were found in rolling condition. Single-phase flow fluctuation, which fluctuates in sinusoidal wave, is directly induced by rolling motion, while two-phase flow fluctuation is supposed to be in annular flow regime which is accompanied with fluctuation caused by rolling motion. Trough-type flow oscillation is confirmed as the boiling incipience according to the pressure drop and heat transfer characteristics. As intermittent boiling occurs at the section close to the outlet of the test channel, during trough-type flow oscillation, two wave peaks in one rolling period are found in the pressure drop fluctuation of the outlet section of the channel. The method of Fast Fourier Transform (FFT) is used to analyze the coupled flow oscillation, and two frequencies, including the rolling frequency and PDO frequency, are found in the amplitude spectrum. Thus, the coupled flow oscillation is supposed to be superposition of trough-type flow oscillation and PDO. Besides, the coupling mechanisms of the coupled flow oscillation are discussed and the evolution characteristics of flow instabilities are presented.